2014
DOI: 10.1055/s-0033-1355546
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging-Guided Prostate Biopsy: Institutional Analysis and Systematic Review

Abstract: !Objectives: To evaluate the detection rate of prostate cancer (PCa) after magnetic resonance-guided biopsy (MRGB); to monitor the patient cohort with negative MRGB results and to compare our own results with other reports in the current literature. Materials and Methods: A group of 41 patients was included in this IRB-approved study and subjected to combined MRI and MRGB. MRGB was performed in a closed 1.5 T MR unit and the needle was inserted rectally. The follow-up period ranged between 12 and 62 months (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…A total of 12 systematic reviews [11][12][13][14][15][16][17][18][19][20][21][22] were relevant and met the preplanned inclusion criteria; however, none of them covered both of the guideline objectives or used the same study selection criteria as ours. A total of 8663 original studies in English were identified and 15 were analyzed.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of 12 systematic reviews [11][12][13][14][15][16][17][18][19][20][21][22] were relevant and met the preplanned inclusion criteria; however, none of them covered both of the guideline objectives or used the same study selection criteria as ours. A total of 8663 original studies in English were identified and 15 were analyzed.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Histopathology specimens were obtained by either transrectal ultrasound or MR-guided biopsy [14]. If radical prostatectomy was performed (13/64 patients), wholemount step section was used as the reference standard.…”
Section: Standard Of Referencementioning
confidence: 99%
“…This method shows a very high accuracy, but it also has certain restrictions in relation to clinical routines such as the discomfort of the patient position and the long duration [6]. The second approach uses cognitive fusion whereby the clinician assigns each suspicious lesion on mpMRI findings to a predefined region of the prostate and aims to hit that specific region using transrectal ultrasound (TRUS) guidance [7].…”
Section: Introductionmentioning
confidence: 99%